Intranasal Vaccination With Lipoproteins Confers Protection Against Pneumococcal Colonisation - Voß, Franziska; Kohler, Thomas P.; Meyer, Tanja; Abdullah, Mohammed R.; van Opzeeland, Fred J.; Saleh, Malek; Michalik, Stephan; van Selm, Saskia; Schmidt, Frank; de Jonge, Marien I.; Hammerschmidt, Sven (Frontiers in Immunology, 2018)
Streptococcus pneumoniae is endowed with a variety of surface-exposed proteins representing putative vaccine candidates. Lipoproteins are covalently anchored to the cell membrane and highly conserved among pneumococcal serotypes. Here, we evaluated these lipoproteins for their immunogenicity and protective potential against pneumococcal colonisation. A multiplex-based immunoproteomics approach revealed the immunogenicity of selected lipoproteins. High antibody titres were measured in sera from mice immunised with the lipoproteins MetQ, PnrA, PsaA and DacB. An analysis of convalescent patient sera confirmed the immunogenicity of these lipoproteins. Examining the surface localisation and accessibility of the lipoproteins using flow cytometry indicated that PnrA and DacB were highly abundant on the surface of the bacteria. Mice were immunised intranasally with PnrA, DacB and MetQ using cholera toxin subunit B (CTB) as an adjuvant, followed by an intranasal challenge with S. pneumoniae D39. PnrA protected the mice from pneumococcal colonisation. For the immunisation with DacB and MetQ, a trend in reducing the bacterial load could be observed, although this effect was not statistically significant. The reduction in bacterial colonisation was correlated with the increased production of antigen-specific IL-17A in the nasal cavity. Immunisation induced high systemic IgG levels with a predominance for the IgG1 isotype, except for DacB, where IgG levels were substantially lower compared to MetQ and PnrA. Our results indicate that lipoproteins are interesting targets for future vaccine strategies as they are highly conserved, abundant and immunogenic.